Lexical semantic fields on textbook for reading course in Universitas Negeri Malang - Nurhidayati, Nurhidayati; Kholisin, Kholisin; Irhamni, Irhamni; Abdul Jabar, Mohd Azidan bin; Dzulfikri, Dzulfikri (citeus, 2023)
This study aims to describe the lexical semantic fields of reading textbooks in Universitas Negeri Malang, specifically in categories being, cosmic, energetic, substantial, terrestrial, objective, living, animate, and human. It used a descriptive qualitative method with a semantic analysis approach. The semantic approach was selected since we intended to comprehend the semantic phenomenon from the lexical-semantic field aspect of a specific textbook course. In detail, we started the research by describing the lexical-semantic field in the textbook and classified the words and phrases. Further, we identified the rational understanding of those words and phrases as a complete understanding of a word requires comprehending the connection with the surrounding words, known as the semantic field. The interconnection of words’ meanings is caused by their specific meaning in particular social situation and condition. Our analysis results suggested that the lexical-semantic field in the reading course textbook (Al-Arabiyah Baina Yadaika chapter 1) from Universitas Negeri Malang is dominated by the being and human semantic fields. Accordingly, the lecturers are suggested to complete the reading textbook with more contextual materials with different semantic fields following students’ interests.